2015
DOI: 10.1128/jvi.00287-15
|View full text |Cite
|
Sign up to set email alerts
|

Marine Snails and Slugs: a Great Place To Look for Antiviral Drugs

Abstract: e Molluscs, comprising one of the most successful phyla, lack clear evidence of adaptive immunity and yet thrive in the oceans, which are rich in viruses. There are thought to be nearly 120,000 species of Mollusca, most living in marine habitats. Despite the extraordinary abundance of viruses in oceans, molluscs often have very long life spans (10 to 100 years). Thus, their innate immunity must be highly effective at countering viral infections. Antiviral compounds are a crucial component of molluscan defenses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 61 publications
0
55
0
Order By: Relevance
“…Due to their filtering activity, marine bivalves are in contact with a high number of viruses, which commonly reach 10 7 particles per milliliter in the ocean, including putative pathogens (36). Due to this fact, they should have a constitutive "ready-to-use" repertoire of antimicrobial molecules that can act in dangerous situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their filtering activity, marine bivalves are in contact with a high number of viruses, which commonly reach 10 7 particles per milliliter in the ocean, including putative pathogens (36). Due to this fact, they should have a constitutive "ready-to-use" repertoire of antimicrobial molecules that can act in dangerous situations.…”
Section: Discussionmentioning
confidence: 99%
“…Mollusks have the potential to be a source of antimicrobial and antiviral compounds, but most members of the phylum Mollusca have not yet been examined for the presence of these bioactive molecules (36). Myticins are examples of the biotechnological and therapeutic potential of bivalves, which are currently limited to serving as a food supply, and may represent an added value for their culture.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, hundreds of marine-based bioactive molecules have been discovered with several undergoing clinical trials (Mayer, Rodríguez, Taglialatela-Scafati, & Fusetani, 2013;Suleria, Masci, & Globe, 2015). These bioactive molecules show anti-bacterial, anti-fungal, anti-cancer, anti-viral, as well as anti-inflammatory activities that can be used to promote the health status of humankind (Dang, Benkendorff, Green, & Speck, 2015;Sugiura, Nagayama, Kinoshita, Tanaka, & Matsushita, 2015), however, the biological activity of most of the marine compounds is still unclear and under investigation (Blunt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The hemolymph contains hemocyanin as its major constituent (16). However, endogenous antimicrobial peptides are also present or synthesized and secreted into hemolymph upon microbial challenge (11,(17)(18)(19). Several studies reported that the antiviral activity of hemolymph against HSV-1 is related to hemocyanin (20)(21)(22).…”
mentioning
confidence: 99%
“…Recently, it was shown that hemolymph from molluscs has antiviral activity against herpes simplex virus 1 (HSV-1) (11)(12)(13)(14)(15). The hemolymph contains hemocyanin as its major constituent (16).…”
mentioning
confidence: 99%